Sonolência e postura corporal inadequada em sala de aula: A preguiça intermedeia a relação? - Barros, Luciana Marques [UNESP]; Hoshino, Katsumasa [UNESP] (My University, 2011)
Objective: Sleepiness and naps occur in classrooms everywhere in the world. Poor seating posture is also common in classrooms. Even though poor posture causes students to be at risk for developing problems in the vertebral column, the relationship between sleep deprivation and bad postures has not yet received attention. Present study evaluated the viability of such hypothesis of link and tried to disclose other possibly involved factors. Methods: Twenty physicians, ten of whom were orthopedists, evaluated the possible risk to the vertebral column of 23 seating postures depicted in photos. Thirty-two skilled teachers testified they had frequently detected the occurrence of those postures displayed in the photos evaluated with the highest risk. Results: According to them, habit (90%), sleep deprivation (24%) and laziness (11%) are the main causal factors of these postures. Interviews carried-out with 50 scholars, 8 to 14 years old, both sexes, revealed that part of them has sleep debit frequently and gave additional information confirming it. Sleepiness during lessons was reported by 39 (78%) among 50 students and 22 (44%) of them said to have slept at least once during lessons. Sleepiness and laziness in the day following sleep reduction was recognized by 96% of the students, and 92% reported to sit differently on those days. Conclusion: The obtained data seems to grant the pertinence of the hypothesis that sleep deprivation can be correlated to high risk bodily postures in classrooms and allows us to hypothesize about laziness involvement in this relationship.
Sleepiness and inadequate bodily posture in classroom: Does laziness intermediate a relationship?
Keywords: Arousal/physiology; Child; Human; Human body; Low back pain/diagnosis; Posture; Schools; Sleep deprivation; Sleep stages; Spine/physiology